Social Media Promotion Strategy of Homestays Based on SWOT Analysis Case Study at Banyuanyar Village Boyolali Regency - Kusumaningrum, Trias Pungkur; Alin, Ariel Yonatan; Farida, Dita Aulia Rachma Nurul (Politeknik NEST, 2025)
This study examines the effectiveness of social media in promoting homestays in Banyuanyar Village, Boyolali Regency. With 27 homestays across its 9 hamlets, the village has significant tourism potential, but limited visitor numbers indicate a need to improve homestay promotion. Using a SWOT analysis, the researchers identified the village's strengths (adequate homestays, clear facility standards, competitive rates, thematic tours) and weaknesses (inefficient reservations, weak promotion, lack of standardization). Opportunities include growing thematic tourism, digital media usage, and partnerships, while threats involve competition and dependence on events. Strategies proposed include enhancing digital promotion, developing thematic tour packages, improving the reservation system, and increasing manager confidence. By leveraging strengths, minimizing weaknesses, seizing opportunities, and mitigating threats, the village can boost homestay occupancy and support sustainable tourism development. The findings provide practical insights for rural tourism communities seeking to effectively promote their homestay accommodations.